2000
DOI: 10.1034/j.1600-0854.2000.011204.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the Vertebrate Nuclear Pore Complex by Biochemical Criteria

Abstract: The nuclear pore is a large and complex biological machine, mediating all signal-directed transport between the nucleus and the cytoplasm. The vertebrate pore has a mass of ~120 million daltons or 30 times the size of a ribosome. The large size of the pore, coupled to its tight integration in the nuclear lamina, has hampered the isolation of pore complexes from vertebrate sources. We have now developed a strategy for the purification of nuclear pores from in vitro assembled annulate lamellae (AL), a cytoplasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 99 publications
1
5
0
Order By: Relevance
“…As expected, the cytoplasmic pore complexes labeled by mAb414 were almost completely overlapped with the staining of RanBP2, which was used a marker for the RanBP2/RanGAP1*SUMO1/Ubc9 complexes ( Fig 4B ). Consistent with the previous studies [ 12 , 60 , 62 ], we found that ~98% of the mAb414-labeled cytoplasmic foci of ALPCs are associated with the network of ER stained by anti-calreticulin antibody after analyzing 50 cells (~12 foci/cell) ( Fig 4A ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, the cytoplasmic pore complexes labeled by mAb414 were almost completely overlapped with the staining of RanBP2, which was used a marker for the RanBP2/RanGAP1*SUMO1/Ubc9 complexes ( Fig 4B ). Consistent with the previous studies [ 12 , 60 , 62 ], we found that ~98% of the mAb414-labeled cytoplasmic foci of ALPCs are associated with the network of ER stained by anti-calreticulin antibody after analyzing 50 cells (~12 foci/cell) ( Fig 4A ).…”
Section: Resultssupporting
confidence: 92%
“…Several karyopherins, including importin α/β and CRM1, have been shown previously to be associated with both NPCs and ALPCs in Xenopus eggs and mouse embryonic fibroblasts [ 60 , 62 , 69 ]. We therefore further hypothesized that the partition of importin α/β and CRM1 between NPCs and ALPCs is also determined by the relative levels of these two pore complexes.…”
Section: Resultsmentioning
confidence: 99%
“…S1A). This was further confirmed by immunostaining neurons for specific nucleoporins known to be incorporated into AL such as Nup98 (Miller and Forbes, 2000) and more importantly, Nup88 (Wu et al, 2001) that interacts with Nup358 at the cytoplasmic side of the NPC (Bernad et al, 2004) (Fig. S1B,C).…”
Section: Nup358 Associates With the Aismentioning
confidence: 57%
“…We examined assembled pores for the Nup160 complex. Annulate lamellae (AL), cytoplasmic stacks of membranes that contain abundant pores identical to nuclear pores, can easily be assembled in Xenopus extracts in vitro ( Dabauvalle et al, 1991 ; Cordes et al, 1995 ; Meier et al, 1995 ; Miller et al, 2000 ; Miller and Forbes, 2000 ). AL were formed in egg extract, purified, and treated with 0.5 M NaCl to partially solubilize the pores ( Miller et al, 2000 ).…”
Section: Resultsmentioning
confidence: 99%